2019
DOI: 10.1167/iovs.19-26560
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of U.S. Food and Drug Administration–Approved Monoaminergic Drugs Protects the Retina From Light Damage in Diverse Models of Night Blindness

Abstract: PurposeThe purpose of this study was to test the extent of light damage in different models of night blindness and apply these paradigms in testing the therapeutic efficacy of combination therapy by drugs acting on the Gi, Gs, and Gq protein-coupled receptors.MethodsAcute bright light exposure was used to test susceptibility to light damage in mice lacking the following crucial phototransduction proteins: rod transducin (GNAT1), cone transducin (GNAT2), visual arrestin 1 (ARR1), and rhodopsin kinase 1 (GRK1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Numerous other studies in rodents investigating retinal degeneration after ONC also found a decrease of the RNFL and TRT, as well as a loss of retinal ganglion cells ( 26 29 ). After a light-induced retinal damage, authors essentially found degeneration of the ORL and photoreceptors, in line with our results ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous other studies in rodents investigating retinal degeneration after ONC also found a decrease of the RNFL and TRT, as well as a loss of retinal ganglion cells ( 26 29 ). After a light-induced retinal damage, authors essentially found degeneration of the ORL and photoreceptors, in line with our results ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…Retina whole mounts for cone population analyses were performed as described earlier ( Leinonen et al, 2019 ). In brief, the superior side of each eye was marked with a permanent marker before enucleation.…”
Section: Methodsmentioning
confidence: 99%
“…Histology and OCT were performed as described earlier (Leinonen et al 2019;Leinonen 2020). OCT imaging using a Bioptigen spectral-domain OCT device (Leica Microsystems Inc., Buffalo Grove, IL) was performed after the in vivo ERG recordings while the animals were under the same anesthesia (vehicle-treated VCP mice, n=5; CB-5083-treated VCP mice, n=4; non-treated WT mice, n=3).…”
Section: Histology and Optical Coherence Tomography (Oct)mentioning
confidence: 99%